Synthesis of Pure Micro- and Nanopyrite and Their Application for As (III) Removal from Aqueous Solution - Guobao Chen; Zhangfu Zhu; Yong Qin (Advances in Materials Science and Engineering)
Arsenic is one of the materials that has a worldwide concern because of its high toxicity and chronic effects on human health. The existence of arsenic as As (III) is about 56 times poisonous as As (V) and more difficult to process. The investigation takes the pyrite as an adsorbent to remove As (III) from waste water. Different morphology and granularity of pyrite were synthesized by hydrothermal and liquid-phase precipitation methods, respectively. The findings show that the addition of pyrite nanoparticles to the solution provided highest As (III) removal efficiency of 88.53%. 1 gL−1 pyrite nanoparticles can reduce the concentration of arsenite in the waste water from an initial As content of 30 mgL−1 to 3.4 mgL−1 at pH 11. Under the similar operating conditions, the synthetic micropyrite and natural pyrite have a lower As (III) removal; both were less than 70%. In addition, the synthetic pyrite nanowires obtained 86.70% removal efficiency of arsenite. The results confirmed that the morphology and granularity of pyrite can significantly influence the adsorption of arsenite removal from aqueous solution.